PENGARUH NATRIUM METABISULFIT (Na2S2O5) TERHADAP WARNA GELATIN KULIT KAKAP MERAH - Suprihatin Suprihatin; Iwan Yusuf Bambang Lelana; Nurfitri Ekantari (Universitas Gadjah Mada, 2012)
This research aimed to determine natrium metabisulfit concentration influence to gelatin colour quality of red large snapper skin. Gelatin production was begun with dry skin rehydration, boiling water submerging then size decreasing and acetate acid solution (CH3COOH) submerging with pH 3 for 24 hours, skin washing, then refined the skin using blender, then the skin was extracted using water at 90oC temperature for three hours. The extracted gelatin was filtered using filter cloth, dakron and zeolite. The natrium metabisulfit (0%; 0.25%; 0.5%; 0.75%; 1%, w/w) was added into the filtrate then the filtrate was dried in an oven with 700C for 36 hours. The gelatin leaves was refined using blender. The result of this research shown that natrium metabisulfit concentration influenced (p<0.05) ash content, sulfide residue, and gelatin colour, but did not influence (p>0.05) the water content, viscosity, and gelatin gel power. The increasing of natrium metabisulfit concentration were followed by gelatin colour qualities which were getting brighter, while ash contents and sulfide residues which were collected were increasing above the Indonesia National Standard. Natrium metabisulfit concentration 0,25% gave the best result based on Indonesia National Standard 01-3735-1995 compared with other treatments, with specifications : protein content 86.64%, ash content 3.45%, water content 7.52%, sulfide residue 313.61 ppm, viscosity 9.58 cPs, gel power 274.82 bloom, and light yellow colour (2.5 Y 7/4).